Factores que afectan la transferencia de tecnología: el caso de la implementación de un sistema de control de producción en hatos lecheros a pequeña escala - Pérez Acevedo, Efraín (Universidad Michoacana de San Nicolás de Hidalgo, 2005)
The transference of technology, referring to its own complexion, requires better results than those produced by some disciplinary research schemes. It depends on different systems of approach as same as on farm research to be successful. Developing countries require of high and efficient schemes to transfer technology, in order to reduce the economic and social gap among them and developed countries to face globalization. Under the present circumstances, it is necessary to identify those factors which impede the transference of technology, particularly the one applied to vulnerable units of rural production. Thirty six (36) units of production have been joined to be closely monitored from October 2003 to March 2004. The work was based on a planned flowchart. The gathering of the information was carried out by stages and its analysis was realized by following the CATMOD procedure (SAS 8.0 ver, 1999). The results showed that there were some aspects, ones related to individual farming, like the educational level, age, kind and location of the farm, etc., other aspects related to the social level, like the way they organize themselves into small farm communities, and other external factors as the lack of continuity in the technical assistance from the extension service office. All of them became important factors which affected the entire process of transference of technology. As a summary, the studied production units showed similar agro climatic conditions as well as big technical, economic, social and cultural differences, all of them which make relevant and fast improvements in the strategies for getting transference of technology.

La transferencia de tecnología, en virtud de su complejidad, va más allá? de los enfoques disciplinarios de investigación. Esta actividad es prioritaria en el avance económico y social de los países en desarrollo, con objeto de reducir la brecha tecnológica y económico-social entre éstos y los países desarrollados. Frente a esta situación es necesario identificar los factores que obstaculizan la transferencia de tecnología aplicada a unidades de producción rural vulnerables a la globalización. Se integraron 36 unidades de producción monitoreadas de octubre del 2003 a marzo del 2004, donde el trabajo fue basado en un organigrama de planeación. La colección de información se realizó por etapas y su análisis por el procedimiento CATMOD (SAS ver 8.0, 1999). Los resultados relacionan a la escolaridad, la edad, tipo de establo y ubicación del mismo, en relación con los productores en lo individual, y la organización social, como los principales factores que afectan al proceso de transferencia por parte de los productores, así como la falta de continuidad en las visitas programadas y las fallas de tipo organizativo, como los dos factores más relevantes en relación a la agencia extensionista. Se concluye que las unidades de producción muestran similares rasgos agro climáticos, pero grandes diferencias socio-culturales y técnico-productivas, lo que conlleva a mejorar las estrategias para el cambio tecnológico.
Facultad de Medicina Veterinaria y Zootecnia. Maestría en Desarrollo Tecnológico en Sistemas de Producción Animal
Keywords: info:eu-repo/classification/cti/6; FMVZ-M-2005-0002; Tecnología; Escolaridad; Brecha tecnológica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5676